Smartphones, citizen science, and the fight against gender-based violence in rural Tanzania - Chandler Klein; Patty Kostkova; Herry Kasunga; Janet Chapman (Frontiers in Global Women's Health)
IntroductionIn rural regions where gender-based violence (GBV) is rampant and communities are largely offline and off-the-map, technology-enabled interventions are emerging to enhance women's quality of life. These initiatives offer opportunities to empirically test the efficacy of citizen science approaches to anti-GBV efforts and contribute to broader debates on the role of smartphones in women's empowerment. Despite the rapid growth of citizen science-driven GBV projects, rigorous evaluations of their impact remain scarce. At the same time, the presumed link between information communication technology (ICT) access and empowerment—as reflected in target 5.b of the UN Sustainable Development Goals (SDG)—remains contested, with empirical studies often suffering from methodological and conceptual shortcomings.MethodsWe seek to fill this gap and produce insights relevant to community-based organizations (CBOs), governments, international bodies, and others tackling GBV and digital exclusion. We do this through a mixed-method approach, guided by contribution analysis (CA) as the mode of logical enquiry. We also apply a novel adaptation of Warshauer's framework of ICT access and Cattaneo and Chapman's model for empowerment to rigorously unpack the variables and the relationship between them. This work represents the first time these two conceptual models have been combined. It also serves as a rare example of a related empirical work offering high-resolution conceptual clarity. Specifically, it relies on primary survey and in-depth interview data collected from a range of project stakeholders in close collaboration with the two implementing CBOs.ResultsThe findings reflect positively on citizen science methodologies, demonstrating their cost-effectiveness, role in fostering informed communities, and ability to capture locally-grounded observations that would otherwise be out of reach. The results indicate a rise in GBV response interventions due to improved case identification using the approach. However, the link between smartphone access and personal empowerment is weak. Digital competency skills development was measurable but did not surpass a basic level. Smartphones were primarily used for entertainment and socializing rather than for improving life chances.DiscussionThese findings challenge the assumption that digital access alone is a catalyst for empowerment. While being offline arguably begets marginalization, findings suggest the reverse is equally true: the marginalized have less chance to translate device ownership into meaningful access. Thus, we cannot rest on providing devices and training alone. Solutions must be holistic and take into account the social embeddedness of technology.